Molecular underpinnings of Th17 immune-regulation and their implications in autoimmune diabetes. Issue 2 (February 2015) - Kumar, Prabhakaran; Subramaniyam, Ganesan
Highlights Recent findings in transcriptional and post-transcriptional mechanisms involved in Th17 cell polarization are discussed. Mechanisms imposing pathogenicity of Th17 cells and their conversion to Th1-like cells are summarized. Role of Th17 immunity in autoimmune diabetes is critically reviewed.